Finite element study of metacarpophalangeal joint silicone implants - Abdul Kadir, Mohammed Rafiq; Kamsah, N.; Aminullah, M. A. (Springer Berlin Heidelberg, 2008)
Surgical treatment of diseased Metacarpophalangeal joint normally use silicone-based prosthesis as joint replacement. Even though mobility is restored to the joint, there have been reports of complications associated with implant instability and wear. In this study, two commercially available silicone prostheses for metacarpophalangeal joint replacement — the Swanson and the Neuflex — were reconstructed and analysed using three dimensional finite element analysis. Computed tomography dataset of the middle finger was used to construct the joint and a load was applied to the proximal interphalangeal joint to simulate flexion. An inhouse experimentally validated algorithm was used to calculate and display interface micromotion between the implant and the bone. Results showed high stress field at the hinge of both implants, with pistoning behaviour of the stems relative to the bone canals. The Neuflex prosthesis had larger stress magnitudes at the hinge, and flexed more than the Swanson for the same magnitude of flexion load. Due to the flexibility of the Neuflex, the pistoning behaviour during flexion was less than the Swanson.